2009
DOI: 10.1038/mt.2009.142
|View full text |Cite
|
Sign up to set email alerts
|

Dose Optimization for Long-term rAAV-mediated RNA Interference in the Nigrostriatal Projection Neurons

Abstract: Short-hairpin RNA (shRNA)-mediated gene knockdown is a powerful tool for targeted gene silencing and an emerging novel therapeutic strategy. Recent publications, however, reported unexpected toxicity after utilizing viral-mediated shRNA knockdown in vivo. Thus, it is currently unclear whether shRNA-mediated knockdown strategy can be used as a safe and efficient tool for gene silencing. In this study, we have generated rAAV vectors expressing shRNAs targeting the rat tyrosine hydroxylase (TH) mRNA (shTH) for te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 28 publications
2
60
0
Order By: Relevance
“…Subsequently, several other groups reported that shRNA overexpression from AAV vectors, most using the strong U6 promoter, causes cytotoxicity in different cell types and organs (McBride et al, 2008;Boudreau et al, 2009;Bish et al, 2011;Martin et al, 2011). Lowering the AAV dose reduced the adverse effects (Grimm et al, 2006;Ulusoy et al, 2009;Ehlert et al, 2010), suggesting that the toxic effect is dependent upon shRNA levels, a result supported by our findings. Analysis of cellular microRNAs was carried out in several of these studies, and the results showed that some microRNAs were decreased to various levels, but others were not changed (Grimm et al, 2006(Grimm et al, , 2010Witting et al, 2008;Ahn et al, 2011;Bish et al, 2011;Martin et al, 2011;Pan et al, 2011).…”
Section: Discussionsupporting
confidence: 86%
“…Subsequently, several other groups reported that shRNA overexpression from AAV vectors, most using the strong U6 promoter, causes cytotoxicity in different cell types and organs (McBride et al, 2008;Boudreau et al, 2009;Bish et al, 2011;Martin et al, 2011). Lowering the AAV dose reduced the adverse effects (Grimm et al, 2006;Ulusoy et al, 2009;Ehlert et al, 2010), suggesting that the toxic effect is dependent upon shRNA levels, a result supported by our findings. Analysis of cellular microRNAs was carried out in several of these studies, and the results showed that some microRNAs were decreased to various levels, but others were not changed (Grimm et al, 2006(Grimm et al, , 2010Witting et al, 2008;Ahn et al, 2011;Bish et al, 2011;Martin et al, 2011;Pan et al, 2011).…”
Section: Discussionsupporting
confidence: 86%
“…The GFP vector contained a FLEX cassette (66) resulting in Cre-dependent expression. The AAV vectors were produced using a double-transfection method with the appropriate transfer plasmid and the helper plasmid containing the essential adenoviral packaging genes, as described previously (67). Vectors were purified by iodixanol step gradients and Q Sepharose column chromatography (Sigma-Aldrich).…”
Section: Methodsmentioning
confidence: 99%
“…In this study not only TH was diminished, but also the expression of VMAT2. In subsequent experiments with low titer AAV5-GFP injections this effect was not seen anymore (Ulusoy et al, 2009). We speculate that in our case, the high tropism of AAV7 for DAergic neurons induces more GFP expression, and as a consequence causes DAergic neurotoxicity.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 95%
“…In the mouse SN, AAV vectors with the SYN promoter were superior to the AAV vectors containing the CMV promoter. In contrast, in the rat, a range of promoters have been used very successfully to direct the transgene expression in the DAergic neurons of the SN via an AAV vector including the CMV (McFarland et al, 2009), CBA (Burger et al, 2004;Klein et al, 2006;Paterna et al, 2004;Ulusoy et al, 2009), CMV/CBA hybrid (Klein et al, 2008) and PDGV (Paterna et al, 2000)) promoters. This suggests that for experiments in the rat the choice of the promoter is not as critical as it appears to be for the mouse.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
See 1 more Smart Citation